2022
DOI: 10.15376/biores.18.1.143-160
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation characteristics of crushed cane tail straw

Abstract: To gain insight into the mechanical properties of crushed sugarcane tail leaves during stress relaxation, a self-made compression equipment was used in this study. The variation law of different factors on the stress relaxation process of crushed cane tail was explored and a stress relaxation model was established. The three-element and five-element generalized Maxwell models were selected to fit the regression analysis of the stress relaxation curve of the crushed cane tail. The comparison showed that the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The tests showed that l DL has a bearing on the mechanical properties of dry ice pellets and on the extrusion force used in the process. This is in line with the conclusions of the relevant studies on pelletizing of wood chips [26], straw [27], and other particulate materials [28].…”
Section: Resultssupporting
confidence: 91%
“…The tests showed that l DL has a bearing on the mechanical properties of dry ice pellets and on the extrusion force used in the process. This is in line with the conclusions of the relevant studies on pelletizing of wood chips [26], straw [27], and other particulate materials [28].…”
Section: Resultssupporting
confidence: 91%
“…In a study on the mechanical properties of sugarcane, Duan et al (2018) used uniaxial confined compression, uniaxial loading and unloading, and consolidation-drainage triaxial and direct shear tests to reveal the static mechanical properties of sugarcane milling mixtures. Lei et al (2023) considered the stress relaxation characteristics of crushed SEL, to explore the changing law of different factors on the stress relaxation process of crushed SEL and to establish a five-component stress relaxation model with a higher coefficient of determination R 2 . Luo et al (2016a,b) tested the tensile, compressive and flexural mechanical properties of sugarcane stalks and found that the tensile and compressive strengths, flexural strengths, and flexural modulus of elasticity of sugarcane stalks decreased significantly from the center of the stalk towards the growth point of the stalk tip (Zheng et al 2017).…”
Section: Introductionmentioning
confidence: 99%